"Through others we become ourselves": The dialectics of predictive coding and active inference. (2020) - Bolis, Dimitris; Schilbach, Leonhard
Abstract: Thinking through other minds creatively situates the free-energy principle within real-life cultural processes, thereby enriching both sociocultural theories and Bayesian accounts of cognition. Here, shifting the attention from thinking-through to becoming-with, we suggest complementing such an account by focusing on the empirical, computational, and conceptual investigation of the multiscale dynamics of social interaction.